Management of the Integration of the National Curriculum and Islamic Boarding Schools in Improving the Quality of Graduates from Islamic Boarding Schools - Ade Mahmud; Nana Herdiana Abdurrahman; R. Supyan Sauri; Ida Tejawiani; Abdul Holik (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2026)
The integration of the national curriculum and the Islamic boarding school (pesantren) curriculum is often limited to combining religious and general subjects, while its management process remains underexplored. This study examines curriculum integration management in improving graduate quality at Daarul Muttaqin and Al Mansyuriyah Islamic Boarding Schools. A qualitative multi case study was conducted using in-depth interviews, participant observation, and document analysis involving school leaders, teachers, ustadz, education staff, and curriculum documents. Data were analyzed through condensation, display, conclusion drawing, and cross-site analysis. The findings indicate that curriculum integration is implemented through four management functions: planning, organizing, implementation, and evaluation. These functions generate four interconnected dimensions of integration: academic integration, character integration, student potential development, and educational governance. Academic integration aligns religious, general, and vocational learning; character integration is strengthened through pesantren values; student development emphasizes leadership, life skills, entrepreneurship, and community engagement; while governance integration is supported by collaborative curriculum planning, continuous monitoring, parental involvement, and quality assurance. The study proposes a Conceptual Model of Curriculum Integration Based on Educational Management, demonstrating that sustainable graduate quality depends on a holistic management system integrating academic, character, developmental, and governance dimensions.